2009
DOI: 10.18553/jmcp.2009.15.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of the Effects of Office-Based Generic Drug Sampling on Antibiotic Drug Costs and First-Line Antibiotic Prescribing Ratios

Abstract: R ising health care costs continue to prompt health plans, among other stakeholders, to identify and promote costeffective health care services. There is an inherent value in the promotion of lower-cost drug therapies (e.g., generic drugs) that achieve the same outcome as a higher-cost drug. 1 ABSTRACT BACKGROUND: Health plans and members benefit from the substitution of lower-cost drug therapies that achieve the same clinical outcomes as higher-cost drugs. Previous research suggests that generic sampling prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Research on this strategy is ongoing, and appears promising. [15][16][17][18] A similar strategy to stocking generic samples is offering vouchers for generic medications that a prescriber could provide to the patient in lieu of a sample. 19 This would potentially offer the same benefits as a generic sample, but without the administrative issues of restocking, managing inventory, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Research on this strategy is ongoing, and appears promising. [15][16][17][18] A similar strategy to stocking generic samples is offering vouchers for generic medications that a prescriber could provide to the patient in lieu of a sample. 19 This would potentially offer the same benefits as a generic sample, but without the administrative issues of restocking, managing inventory, etc.…”
Section: Discussionmentioning
confidence: 99%
“…1 A similar report describing the result of this initiative on overall rates of generic product use and cost was previously published in the June 2007 issue of JMCP. 2 In the current study examining the impact of the kiosk program on prescribing of antimicrobial drugs specifically, the authors found that rates of "first-line" (generic) antimicrobial use, measured as a proportion of all antimicrobial prescriptions, were similar among network prescribers with versus without access to the medication kiosks (42.0% vs. 41.4%, respectively; P = 0.028) in 2006, the most recent year measured.…”
mentioning
confidence: 86%
“…The authors note that the program targeted high-volume prescribers and those having below average generic use rates. 1,2 Yet no data are provided to present these characteristics in comparison with those of network prescribers without access to the samples kiosks. Stratification according these and other characteristics would have likely yielded interesting findings.…”
Section: Does Facilitating Access To Generic Antibiotics Affect Provimentioning
confidence: 99%
“…Generic drug sampling funded by insurance companies has been shown to significantly increase the use of generic drugs. 25,26 More study of generic sampling is required to determine if the cost of these programs justifies the outcomes that were obtained. 25 Waste associated with sampling.…”
Section: Costmentioning
confidence: 99%